Determining The Best Conditioning Method For Mammothred Daisy(Chrysanthemum Morifolium) ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2023)
Background: Conditioning is a post-harvest step necessary in the maintenance of cut flowers. It not only helps to increase the  shelf life of the cut flowers but also helps in increasing the time for which the flowers can be stored. The process of conditioning  also helps in providing certain key nutrients to the cut flowers which are required for their sustainability. It also protects the  flowers from getting contaminated by several disease-causing microbes. Most people usually do not pay enough attention to this  process which often their beautiful and precious flowers to decay earlier than usual. Proper conditioning method can provide a  solution to all these problems by providing optimum conditions for the flower and protects the cut flowers against early aging. Objective: The study was carried out with the objectives (1) to determine the best conditioning method for cut Mammoth Red  Daisy flowers through scientific experiments and (2) to get views on the flowering behaviour under different conditions based on  visual parameters. Methodology: This study's methodology combined experimental and observational research methods. The  experiment was performed in the on-premises housekeeping lab at IHM Pusa, under the supervision of the research guide and  lab attendant. Through the use of a Google Form-created questionnaire, the observational study was conducted. This  questionnaire was filled out by subject experts in the domain based on the visual parameters from the experiment conducted. Results: Alittle contradictory from the expected, SET'A' was voted the best in visual parameters however the best conditioning  method for the Mammoth Red Daisy was provided by SET 'C' from the experiment conducted which contained a solution of  bleach, citric acid and sucrose, prepared in distilled water. Conclusion: According to the findings of the experiment and the  observations made, it was found that the solution made in distilled water with bleach, citric acid, and sucrose proved to be the  most effective in conditioning the Mammoth Daisy. Thus, it can be inferred that applying the aforementioned solution can  significantly delay the early aging of cut flowers, lengthen their life, and aid in achieving sustainability.
Keywords: Conditioning; Cut-flowers; Floriculture; Vase-life